ASISTENSI MENGAJAR PERSAMAAN DASAR AKUNTANSI PADA PERUSAHAAN JASA DI SMA BUNDA HATI KUDUS - Gracia Agatha Widjaja; Merry Susanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Accounting learning in secondary schools still faces persistent obstacles, especially students’ low interest and limited mastery of concepts. These challenges are largely related to the perception that accounting has little relevance to their field of study and the reliance on conventional lecture-based approaches. To respond to this problem, the Merdeka Belajar–Kampus Merdeka (MBKM) program organized a teaching assistance activity at SMA Bunda Hati Kudus from August to November 2025. The primary goal was to strengthen students’ understanding of basic accounting for service companies by applying Project-Based Learning (PjBL). This learning model was carried out through contextual projects that combined theoretical concepts with practical applications, beginning with transaction recording and continuing to the preparation of simple financial statements. Data collection relied on ongoing evaluations, classroom observations, and project outputs. The findings indicated clear improvements in conceptual comprehension, precision in completing accounting cycles, and students’ motivation to learn. Furthermore, the MBKM Teaching Assistance Program created a more engaging classroom atmosphere and fostered essential soft skills such as teamwork and communication among university student mentors. In conclusion, the MBKM teaching assistance program proved effective in enhancing accounting literacy at the high school level, while also highlighting PjBL’s role as an innovative instructional strategy and strengthening collaboration between schools and universities. Pembelajaran akuntansi di sekolah menengah masih menghadapi berbagai kendala, khususnya rendahnya minat serta keterbatasan pemahaman siswa terhadap konsep dasar. Hal ini berkaitan dengan anggapan bahwa akuntansi kurang relevan dengan bidang mereka serta pola pengajaran yang masih didominasi metode ceramah teoretis. Untuk menjawab tantangan tersebut, program Merdeka Belajar–Kampus Merdeka (MBKM) melaksanakan kegiatan asistensi mengajar di SMA Bunda Hati Kudus pada Agustus hingga November 2025. Tujuan utamanya adalah memperkuat pemahaman siswa terhadap akuntansi dasar perusahaan jasa melalui penerapan Project-Based Learning (PjBL). Model ini dilaksanakan dengan proyek kontekstual yang menghubungkan teori dengan praktik, mulai dari pencatatan transaksi hingga penyusunan laporan keuangan sederhana. Data diperoleh melalui evaluasi berkelanjutan, observasi kelas, serta hasil proyek yang dikerjakan siswa. Hasil kegiatan menunjukkan adanya peningkatan yang nyata dalam pemahaman konsep, ketelitian dalam menyelesaikan siklus akuntansi, serta motivasi belajar. Selain itu, program Asistensi Mengajar turut menciptakan suasana kelas yang lebih partisipatif dan mendorong pengembangan keterampilan komunikasi maupun kolaborasi mahasiswa pendamping. Kesimpulannya, program asistensi mengajar MBKM terbukti efektif dalam meningkatkan literasi akuntansi di tingkat sekolah menengah, sekaligus menegaskan potensi PjBL sebagai pendekatan pembelajaran inovatif serta memperkuat sinergi antara sekolah dan perguruan tinggi.